(untitled) (Vietnam Journal of Community Medicine, 2022)
Objective: To compare the analgesic efficacy of fentanyl, morphine in combination with ketamine and morphine alone after abdominal surgery. Subjects and methods: Prospective clinical, randomized and controlled study on 90 patients undergoing elective abdominal surgery at Vinh Long General Hospital from June 2021 to June 2022. Results: The analgesic effectiveness as lying still was similar between the three groups with the average VAS score at all time points below 3 points. The analgesic effectiveness as moving of the fentanyl group alone and the morphine-ketamine combination group were better than that of the morphine alone group at the time of evaluation on day 2. The percentage of patients with pain relief levels from satisfied or above (all over 90%), A/D ratio (all > 74%) were similar between the three groups. Conclusion: The analgesic effectiveness as lying still was similar between the three groups, while the analgesic effectiveness as moving was better in the fentanyl group and in the morphine-ketamine combination group than in the morphine alone group (day 2).